2020
DOI: 10.3390/md18100510
|View full text |Cite
|
Sign up to set email alerts
|

Blue Mussel-Derived Peptides PIISVYWK and FSVVPSPK Trigger Wnt/β-Catenin Signaling-Mediated Osteogenesis in Human Bone Marrow Mesenchymal Stem Cells

Abstract: Marine-derived bioactive peptides have shown potential bone health promoting effects. Although various marine-derived bioactive peptides have potential nutraceutical or pharmaceutical properties, only a few of them are commercially available. This study presented an osteogenic mechanism of blue mussel-derived peptides PIISVYWK and FSVVPSPK as potential bone health promoting agents in human bone marrow-derived mesenchymal stem cells (hBMMSCs). Alkaline phosphatase (ALP) activity and mineralization were stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…We further detected the promotion effect of the coating on early and late osteogenic differentiation by ALP staining, alizarin red staining, and qRT-PCR. High expression of ALP is essential for the degradation of pyrophosphate in the early stage of osteogenic differentiation, an inhibitor of mineralization ( Jablonská et al, 2020 ; Oh et al, 2020 ; Tao et al, 2020 ; Chen et al, 2021b ). Therefore, rational morphology HA coatings and a low degree of crystalline formation of PS could enhance the osteogenic differentiation of BMSCs at the early stage.…”
Section: Discussionmentioning
confidence: 99%
“…We further detected the promotion effect of the coating on early and late osteogenic differentiation by ALP staining, alizarin red staining, and qRT-PCR. High expression of ALP is essential for the degradation of pyrophosphate in the early stage of osteogenic differentiation, an inhibitor of mineralization ( Jablonská et al, 2020 ; Oh et al, 2020 ; Tao et al, 2020 ; Chen et al, 2021b ). Therefore, rational morphology HA coatings and a low degree of crystalline formation of PS could enhance the osteogenic differentiation of BMSCs at the early stage.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation potential of osteoblasts is subject to various internal and external factors that are regulated by signaling pathways. These signaling pathways include the Wnt/β-catenin ( Oh et al, 2020 ; Park et al, 2020 ), MAPK ( Ge et al, 2007 ), and JAK/STAT ( Levy et al, 1996 ; Joung et al, 2012 , 2013 ; Darvin et al, 2013 ; Yu et al, 2018 ) pathways, which have all been reported to promote osteogenesis in vivo and in vitro . Furthermore, let-7 participates in the JAK2/STAT signaling pathway in cancer cells by targeting SOCS4 and activates the JAK1/STAT3 signaling pathway ( Patel et al, 2014 ; Chen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Type I collagen, osteopontin ( OPN ), osteocalcin ( OCN ), and alkaline phosphatase (ALP) are secreted by cells and have important roles in osteoblast differentiation ( Long, 2011 ). In addition, several signaling pathways, including Wnt/β-catenin ( Oh et al, 2020 ; Park et al, 2020 ), MAPK ( Ge et al, 2007 ), and JAK/STAT ( Levy et al, 1996 ; Joung et al, 2012 , 2013 ; Darvin et al, 2013 ; Yu et al, 2018 ), promote osteogenesis in vivo and in vitro . Furthermore, the persistent activation of the JAK2/STAT5 signaling pathway increases osteoblastic differentiation ( Joung et al, 2012 , 2013 ; Darvin et al, 2013 ; Yu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, many BAPs have been isolated and identified from marine dietary protein hydrolysates [27]. In addition, previous studies have identified specific BAPs in blue mussel protein hydrolysates that have been attributed antioxidant, antithrombotic, antihypertensive, osteogenic, and anti-osteoporotic effects [19,20,[28][29][30][31]. Blue mussel protein hydrolysate produced by α-chymotrypsin has been previously identified as a potential cytoprotective agent [1].…”
Section: Discussionmentioning
confidence: 99%